Adherence to Personal Protective Equipment practices during the COVID-19 pandemic: A pilot study - Taryn B. Amos; Cameron Griffin; Joshua K. Schaffzin; Andrea Ankrum; Felicia Scaggs Huang (Elsevier, 2024)
Summary: A direct observational pilot project of healthcare personnel (HCP) was conducted to validate a tool that measures personal protective equipment (PPE) adherence at a large pediatric institution. Overall unit PPE adherence for all moments ranged from 50-61%. Masking was the most adhered to PPE moment (100%); hand hygiene prior to donning PPE had the lowest adherence (13%). Using data from this standardized tool, researchers can evolve PPE standards to maximize their adherence, effectiveness, and ease of utilization.